A new direction of labor emigration from Central Asian countries to the Republic of Korea in the context of global challenges - A. Kh. Rakhmonov (Вестник университета)
The influx of emigrants from the Central Asian countries to the Republic of Korea (hereinafter referred to as Korea), social and demographic composition of migrants, labor migration as a new direction of migration, labor migration channels from the Central Asian countries, as well as the Labor Agreements among states have been considered. The history of migration among the Central Asian countries and Korea began during the Soviet period, when ethnic Koreans were deported from the border regions of the Russian Soviet Federative Socialist Republic to the republics of Central Asia (Kazakhstan, Kyrgyzstan, Tajikistan, Uzbekistan). A new stage of migration from the Central Asian countries to Korea began after the collapse of the Soviet Union, with ethnic Koreans initially migrating. Ethnic Kyrgyz, Tajiks, and Uzbeks have lost their jobs and started leaving Russia since 2014, after the beginning of the currency crisis, and later, after new economic sanctions implementation against Russia due to the special military operation, as well as stricter migration controls, and some of them have shifted to the Korean labor market. At the same time, Korea and the United Kingdom have begun to attract migrants from the Central Asian countries to their labor markets.